2022
DOI: 10.1016/j.esmoop.2021.100365
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immunoliposomes to EGFR-positive glioblastoma

Abstract: Background:We assessed the capacity of epidermal growth factor receptor (EGFR)-targeted immunoliposomes to deliver cargo to brain tumor tissue in patients with relapsed glioblastoma harboring an EGFR amplification. We aimed to assess the tolerability and effectiveness of anti-EGFR immunoliposomes loaded with doxorubicin (anti-EGFR ILs-dox) in glioblastoma multiforme patients. Patients and methods: Patients with EGFR-amplified, relapsed glioblastoma were included in this phase I pharmacokinetic trial. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 32 publications
(60 reference statements)
0
26
0
1
Order By: Relevance
“…[118] However, the therapeutic effi cacy results in breast cancer remain dismal. [119,120] Depending on the results of the ongoing phaseII clinical trials, [121] the cost of production (antibodies production, NPs synthesis, con jugation, and batch reproducibility) [122,123] versus therapeutic improvement will need further analysis to justify such conju gation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…[118] However, the therapeutic effi cacy results in breast cancer remain dismal. [119,120] Depending on the results of the ongoing phaseII clinical trials, [121] the cost of production (antibodies production, NPs synthesis, con jugation, and batch reproducibility) [122,123] versus therapeutic improvement will need further analysis to justify such conju gation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Low dose of DOX was safe for patients, even with extended (>6 weeks) dosing [146]. Promising results were also observed in phase I trial (GBM-LIPO trial) in which patients with relapsed glioblastoma harboring an EGFR amplification were treated with anti-EGFR doxorubicin-loaded immunoliposomes (anti-EGFR ILsdox) [63].…”
Section: Discussionmentioning
confidence: 96%
“…The anti-EGFR-doxorubicin-loaded immunoliposomes (ILs-DOX) displayed highly efficient binding and internalization in a panel of EGFR and EGFRvIII overexpressing cells [61,62]. Recently, a small trial with anti-EGFR ILs-DOX on relapsed GBMs with EGFR amplification showed positive response in one patient [63].…”
Section: Introductionmentioning
confidence: 99%
“…After a phase 1 dose-escalation trial (NCT01702129) in advanced solid tumors, C225-ILs-Dox was clinically evaluated in patients with relapsed or refractory high-grade gliomas (NCT03603379). Although the delivery of C225-ILs-dox to glioblastoma tissue was demonstrated, no other definitive conclusions can be drawn from this trial, as there was no control group, and only a few patients were treated [ 115 ]. The DOX-loaded PEGylated immunoliposome termed MCC-465 utilizes the F(ab’) 2 fragment of human GAH mAb as the targeting ligand, which positively reacts to over 90% of gastric cancer tissues but negatively to all normal tissues.…”
Section: Antibody-functionalized Lipid Nanoparticles For Anticancer D...mentioning
confidence: 99%